2012 Annual Report of the American Association of Poison Control Centers' National Poison Data System (NPDS): 30th Annual Report. (December 2013) - Mowry, James B.; Spyker, Daniel A.; Cantilena, Louis R.; Bailey, J. Elise; Ford, Marsha
Abstract: Background: This is the 30 th Annual Report of the American Association of Poison Control Centers' (AAPCC) National Poison Data System (NPDS). As of July 1, 2012, 57 of the nation's poison centers (PCs) uploaded case data automatically to NPDS. The upload interval was 7.58 [6.30, 11.22] (median [25%, 75%]) min, creating a near real-time national exposure and information database and surveillance system. Methodology: We analyzed the case data tabulating specific indices from NPDS. The methodology was similar to that of previous years. Where changes were introduced, the differences are identified. Poison center cases with medical outcomes of death were evaluated by a team of 34 medical and clinical toxicologist reviewers using an ordinal scale of 1–6 to assess the Relative Contribution to Fatality (RCF) of the exposure to the death. Results: In 2012, 3, 373, 025 closed encounters were logged by NPDS: 2, 275, 141 human exposures, 66, 440 animal exposures, 1, 025, 547 information calls, 5, 679 human confirmed nonexposures, and 218 animal confirmed nonexposures. Total encounters showed a 6.9% decline from 2011, while healthcare facility (HCF) exposure calls increased by 1.2%. All information calls decreased by 14.8% and HCF information calls decreased by 1.7%, medication identification requests (Drug ID) decreased by 22.0%, and human exposures reported to US PCs decreased by 2.5%. Human exposures with less serious outcomes have decreased by 3.7% per year since 2008, while those with more serious outcomes (moderate, major, or death) have increased by 4.6% per year since 2000. The top five substance classes most frequently involved in all human exposures were analgesics (11.6%), cosmetics/personal care products (7.9%), household cleaning substances (7.2%), sedatives/hypnotics/antipsychotics (6.1%), and foreign bodies/toys/miscellaneous (4.1%). Analgesic exposures as a class increased the most rapidly (8, 780 calls/year) over the last 12 years. The top five most common exposures in children aged 5 years or less were cosmetics/ personal care products (13.9%), analgesics (9.9%), household cleaning substances (9.7%), foreign bodies/toys/ miscellaneous (7.0%), and topical preparations (6.3%). Drug identification requests comprised 54.4% of all information calls. NPDS documented 2, 937 human exposures resulting in death with 2, 576 human fatalities judged related (RCF of 1-Undoubtedly responsible, 2-Probably responsible, or 3-Contributory). Conclusions: These data support the continued value of PC expertise and need for specialized medical toxicology information to manage the more severe exposures, despite a decrease in calls involving less severe exposures. Unintentional and intentional exposures continue to be a significant cause of morbidity and mortality in the US. The near real-time, always current status of NPDS represents a national public health resource to collect and monitor US exposure cases and information calls. The continuing mission of NPDS is to provide a nationwide infrastructure for public health surveillance for all types of exposures, public health event identification, resilience response, and situational awareness tracking. NPDS is a model system for the nation and global public health.